2015
DOI: 10.1007/s11414-015-9492-5
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Treatment Providers and Clients with Serious Mental Illness Regarding Effective Therapeutic Relationships

Abstract: This study explores the nature of clinical therapeutic relationships between mental health treatment providers and high-need clients with serious mental illness who had recently discontinued treatment. Semi-structured qualitative interviews of 56 clients with serious mental illness who had recently discontinued care and 25 mental health treatment providers were completed. Both clients with serious mental illness and treatment providers emphasized the importance of client-focused goal setting, time and availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…talk therapy) after the first visit were significantly fewer for patients who did not have initial medication compliance discussions. Our results reinforce studies that have demonstrated the importance of engaging patients in treatment decisions [6][7][8] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…talk therapy) after the first visit were significantly fewer for patients who did not have initial medication compliance discussions. Our results reinforce studies that have demonstrated the importance of engaging patients in treatment decisions [6][7][8] .…”
Section: Discussionsupporting
confidence: 88%
“…Treatments for SMIs are most effective when patients are actively engaged in the management of their condition, including regular interaction with a clinical professional and adherence to (or compliance with) the prescribed treatment regimen [6][7][8] , which often includes antipsychotic medication. Unfortunately, medication non-adherence is widespread among patients with SMI, with prevalence estimates ranging from 35% to 75% among systematic reviews [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the existing studies, it is clear that the relational dimension of the alliance is crucial for the establishment of a positive therapeutic relationship when working with patients with schizophrenia. For example, Easter et al (2015) stress the value that patients ascribe to talking, feeling that they share common ground with the therapist, having a say in the planning of the treatment, and having a therapist who displays availability and flexibility. As another example, Fenton (2000) indicates that the issue ultimately depends on the therapist's ability to be attuned to the patient's clinical needs.…”
Section: Therapeutic Alliance In Psychotherapy With Patients With Schmentioning
confidence: 99%
“…Several authors have noted the difficulties experienced by therapists when attempting to establish a positive therapeutic relationship with patients with schizophrenia (Easter, Pollock, Pope, Wisdom, & Smith, ; Kvrgic et al., ). This challenge is usually attributed to clinical manifestations of the disorder, which include symptom severity (Johansen, Melle, Cabral Iversen, & Hestad, ), thought alterations (Calvetti, Homan, & Vauth, ), and low patient insight about his or her symptoms (Easter et al., ). More recently, research has explored the negative impact of self‐stigmatization and the positive effect of therapists’ recovery‐focused approach (Kvrgic et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation